Selection of drought tolerant rice varieties for the western mid hills of Nepal - Adhikari, B. B.; Mehera, B.; Haefele, S. M. (Journal of the Institute of Agriculture and Animal Science, 2018)
Rice (Oryza sativa L) is the most important staple food crop in Nepal, but current yields are low and total production varies, mostly due to drought. To evaluate high yielding and drought tolerant rice genotypes in typical rainfed lowland conditions, a participatory varietal selection trials was conducted with farmers in farmer’s field at Sundarbazar, Lamjung, Nepal during the wet season 2009 and 2010. Trials were laid out in a Randomized Complete Block Design with six replications. Results obtained from two years’ experiment indicated that the genotypes IR-74371-54-1 and IR74371-70-1 matured at the same duration as the local check Radha-4 (120-123 days growth duration). Both genotypes had a high average chlorophyll content (SPAD reading of 15.9-16.1), were medium tall (110-112 cm), non-lodging, had a high number of filled grains and little sterility, and a high grain yield (mean yield 5.0 and 4.8 t ha-1, respectively). They also had the highest root length (22.4-26.2 cm) and root weight (9.5-10 g hill-1) which could tolerate more drought than the other genotypes tested. The maximum cost/benefit ratio was found in IR-74371-54-1 (1:1.72) followed by IR-74371-70-1 (1:1.66) and IR-74371-46-1-1 (1:1.65). All three lines were highly preferred by farmers in preference rankings during field visits and were released in Nepal in 2011 as Sookhadhan-2, Sookhadhan-3 and Sookhadhan-1 varieties, respectively. They fit easily into the existing cropping system in rainfed lowlands, are economically viable and safe to cultivate for the farmers in the mid hills of Nepal. Journal of the Institute of Agriculture and Animal Science. Vol. 33-34, 2015, page: 195-206